2018
DOI: 10.1038/s41598-018-24781-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of RNA quality, microarray data reliability and pathway analysis in fresh, fresh frozen and formalin-fixed paraffin-embedded tissue samples

Abstract: Formalin-fixed paraffin-embedded (FFPE) tissues are valuable resources commonly used in pathology. However, formalin fixation modifies nucleic acids challenging the isolation of high-quality RNA for genetic profiling. Here, we assessed feasibility and reliability of microarray studies analysing transcriptome data from fresh, fresh-frozen (FF) and FFPE tissues. We show that reproducible microarray data can be generated from only 2 ng FFPE-derived RNA. For RNA quality assessment, fragment size distribution (DV20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 37 publications
8
64
0
Order By: Relevance
“…All three genes showed the same expression pattern, being FFPE the samples with significant higher Cq values followed by SF, RNL and SF-OCT, respectively. These results are in agreement with those presented by Wimmer et al 19 , who also observed a clear separation between SF and FFPE samples, both in different Bioanalyzer profiles and the higher Cq values observed with GAPDH, G6PD and SDHA reference genes. Therefore, we present reproducible results even though we tested different reference genes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All three genes showed the same expression pattern, being FFPE the samples with significant higher Cq values followed by SF, RNL and SF-OCT, respectively. These results are in agreement with those presented by Wimmer et al 19 , who also observed a clear separation between SF and FFPE samples, both in different Bioanalyzer profiles and the higher Cq values observed with GAPDH, G6PD and SDHA reference genes. Therefore, we present reproducible results even though we tested different reference genes.…”
Section: Discussionsupporting
confidence: 93%
“…It is known that RNA derived from FFPE samples has undergone cross-links, chemical modifications and degradation over time due to the fixation method 17 . These molecular changes support that better quality is usually determined in RNA derived from frozen in comparison with FFPE samples 18,19 although in some cases RNA derived from FFPE was reported to be suitable for gene expression experiments 20 . Today, there are alternative choices for long-term storage of human tissue samples, including RNA preservation solutions.…”
mentioning
confidence: 70%
“…The DV200, a quality parameter for RNA derived from FFPE [54], was calculated using the 2100 Expert software (Supplementary Table 1) (version B.02.08.SI648 (SR2)).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac SOD activity was measured colormetrically at 420 nm by the method that is based on the inhibition of pyrogallol autoxidation by SOD, and the results were expressed as U/g tissue [31]. [33]. The SYBR green data were analyzed with a relative quantification to GAPDH as a reference gene.…”
Section: Evaluation Of Cardiac Oxidative and Nitrosative Stressmentioning
confidence: 99%